Crisis Management Strategies in Facing Global Economic Uncertainty: A Study of MSMEs in Makassar - Hendrawati Hamid (Maneggio, 2025)
Global economic uncertainty presents a significant challenge for Micro, Small, and Medium Enterprises (MSMEs) in Indonesia, particularly in navigating rapid market changes and currency fluctuations. This study aims to analyze the crisis management strategies employed by MSMEs in Makassar in response to global economic uncertainty. A qualitative approach with a case study method was used to explore the adaptation strategies implemented by MSMEs. The results show that MSMEs in Makassar employ various strategies such as product diversification, digital technology utilization, and collaboration with strategic partners. Product diversification enables MSMEs to reach broader markets and reduce dependence on a single product type. Digitalization, through the use of e-commerce platforms and social media, accelerates MSMEs' adaptation to economic uncertainty. Furthermore, partnerships with other businesses and the government play a crucial role in maintaining business continuity. Innovation in financial and operational management, such as more flexible cash flow management, also proves effective. This study shows that MSMEs' ability to adapt and innovate in crisis management strategies is essential to ensuring their sustainability amid global economic crises.